Rapid quantification of bioactive compounds in Salvia miltiorrhiza Bunge derived decoction pieces, dripping pill, injection, and tablets by polarity-switching UPLC-MS/MS - Shen, Qing; Wang, Haixing; Quan, Bin; Sun, Xiuhua; Wu, Guohua; Huang, Darong; Wang, Qingcheng; Luo, Pei (Frontiers in Chemistry, 2022)
Salvia miltiorrhiza Bunge (SMB) has unambiguous biological functions in cardiovascular diseases, thus has been processed into different medicine forms. However, universal analytical method for fast quantification of bioactive compounds in SMB and SMB derived products is still missing. In this study, a polarity switching strategy was developed and optimized, which enabled the detection of the target compound in both positive and negative ion modes in a single run. The MS2 features of each compound were characterized to select the most prominent transitions for quantitative and qualitative analysis. Afterwards, the performance of this method was validated in terms of linearity (≥ 0.9916), limit of detection (LOD, 0.003−0.135 ng·mL−1), limit of quantification (LOQ, 0.010−0.450 ng·mL−1), precision (48.23 ± 2.58 ng·mL−1 to 53.72 ± 3.11 ng·mL−1), recovery (RSD 2.04%−5.79%), and stability (RSD ≤ 7.52%). Finally, the bioactive compounds in SMB and SMB derived products were determined, among which salvianate A, salvianolic acid A, and rosmarinic acid were the main components in all samples. In conclusion, the polarity switching UPLC-MS/MS method is efficient in accurate determining the bioactive compounds, which greatly shorten the time for analysis when compared with conventional methods. It has great potential quality control of SMB and SMB derived products.